Sucker punch [videorecording (DVD)] - Snyder, Zack, 1966-; Browning, Emily, 1988-; Gugino, Carla, 1971-; Malone, Jena, 1984-; Hamm, Jon, 1971-; Hudgens, Vanessa, 1988-; Chung, Jamie, 1983-; Isaac, Oscar; Glenn, Scott, 1942- (Warner Home Video, 2011)
Set in the 1950s, it tells the story of Baby Doll in a mental institution, where she creates an alternate reality. She plans to escape from that imaginary world, but to do that she needs to steal five objects before she is captured by an unknown adversary.